Estudo fitoquímico de Conchocarpus marginatus (Rutaceae), e avaliação do potencial biológico dos compostos isolados - Bellete, Barbara Sayuri (2013)
The specie Conchocarpus marginatus is native from Espírito Santo. This plant, that was recently reclassified by PIRANI e KALLUNKI, does not show chemical or biological data in literature yet. In this way, the phytochemical study of Co. marginatus described in this work, aim to contributed to chemosystematic of Rutaceae family, and a better classification of this genus in the family. The study allowed the isolation and identification of 12 substances, and were found mainly alkaloids derived from antranilic acid. They are: 2-phenyl-1- methyl-quinolin-4-one (11), 2-phenyl-1-methyl-7-methoxy-quinolin-4-one (12), 1-hydroxy-3-methoxy-N-metilacridone (6), Arborinine (7), Methyl-arborinine (8), 1-hydroxy-3,6-dimethoxy-N-metilacridone (10), 1,2,3,6-tetramethoxyacridone (9), 1,2,3,6-tetramethoxy-N-metilacridone (4) e 1-hydroxy-2,3,6- trimethoxy-N-metilacridone (5). The last four substances are new structures. Two different biological assays were performed with some isolated compounds. Assays in vitro of chlorophyll inhibition were performed in chloroplasts isolated from spinach leaves, aiming to found models to new photosynthesis inhibitor herbicides, by study of Chl a fluorescence. Substances isolated from Co. marginatus analysed in this assay were active, and the substance 9 was the most active in Chl a fluorescence measures. This result indicates that this molecule could damage the OEC complex and one of his action site is located in FSII, binding to Qa environment. In cytotoxic assays, the substance 6 is the more promising molecule against cancerígenas MCF-7 (breast adenocarcinoma), NCI-460 (non-small cell lung cancer) and A375-C5 (melanoma) cancer cells, showing respectively GJ50 values of 25, 20 e 22 μM.